2019
DOI: 10.1002/anie.201901045
|View full text |Cite
|
Sign up to set email alerts
|

Full‐Spectrum Persistent Luminescence Tuning Using All‐Inorganic Perovskite Quantum Dots

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(60 citation statements)
references
References 47 publications
(20 reference statements)
3
57
0
Order By: Relevance
“…Exciton confinement in small volumes leads to an increase in exciton binding energy, may resulting in an enhancement of the radiative recombination mediated by excitons rather than free electron and holes. [ 23 ] Unfortunately, few study reported inorganic perovskites nanocrystals as LPL materials, [ 24 ] because the LPL output is the mutual cooperation of activator and defect centers. [ 25 ] Although inorganic perovskites yields attractive emission as direct bandgap semiconductors, defect states acting as effective trapping centers that can capture and liberate carriers for the subsequent migration to the emission centers [ 26 ] are absence from the perovskites.…”
Section: Introductionmentioning
confidence: 99%
“…Exciton confinement in small volumes leads to an increase in exciton binding energy, may resulting in an enhancement of the radiative recombination mediated by excitons rather than free electron and holes. [ 23 ] Unfortunately, few study reported inorganic perovskites nanocrystals as LPL materials, [ 24 ] because the LPL output is the mutual cooperation of activator and defect centers. [ 25 ] Although inorganic perovskites yields attractive emission as direct bandgap semiconductors, defect states acting as effective trapping centers that can capture and liberate carriers for the subsequent migration to the emission centers [ 26 ] are absence from the perovskites.…”
Section: Introductionmentioning
confidence: 99%
“…Long persistent luminescence (LPL) materials,a lso known as afterglow or long-lasting phosphorescence materials,have aroused extensive attention due to their long triplet excited state and potential applications in bioimaging, [1] anticounterfeiting, [2] data encryption, [3] light-emitting diodes, [4] phosphorescence lasing [5] and so forth. In the past decades, numerous materials with LPL phenomenon have been developed, including inorganic metal oxides, [6] carbon quantum dots, [7] perovskites, [8] organic polymers, [9] pure organic phosphors [10] and metal-organic materials. [11] Besides the pursuit of long LPL lifetime and high brightness,the controllable and tunable LPL color is another important attribute when applying these materials.…”
Section: Introductionmentioning
confidence: 99%
“…Solid‐state luminescent materials with long persistent luminescence (LPL) have attracted extensive interest due to their fascinating photophysical phenomena and potential applications in bio‐imaging, photodynamic therapy, anticounterfeiting, OLEDs, photocatalysis, and so on. Many materials with LPL characteristics have been studied, such as inorganic oxide materials, perovskites, polymers, pure organic phosphors, and metal–organic materials . MOFs have attracted special attention due to their flexible structural design and outstanding properties.…”
Section: Introductionmentioning
confidence: 99%